COLLABORATION SKILLS OF STUDENTS ON THE IMPLEMENTATION OF OHM LAW PRACTICUM ASSISTED BY PHET SIMULATION - Juita, Dewi; M, Yusmaridi (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
Students' collaboration skills are very important to support the 21st century skills of future students. Students can show a good attitude of working together in solving problems, working according to roles, working together in effective time, and providing appropriate assistance between team members. The collaboration skills referred to in this study consist of 13 sub-indicators that are well explained. The purpose of this study was to determine the achievement of student collaboration skills by using virtual simulation in the form of phet simulation in ohm law practicum activities. The instrument used is a performance assessment sheet of collaboration skills based on a clear performance assessment rubric. The method used is descriptive method with quantitative approach. The results showed that the average achievement of student collaboration skills was 84% in the good category. The results showed that of the 13 indicators of collaboration skills, there were 3 indicators whose achievements were very good, namely students being able to divide their group work fairly, students being able to help team members in solving problems, and students being able to solve problems without involving lecturers.